2019
DOI: 10.1002/ajhb.23250
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the vitamin D receptor gene is associated with maternal vitamin D concentration and neonatal outcomes: A Brazilian cohort study

Abstract: Objectives: This study evaluated the associations between single-nucleotide polymorphisms (SNPs) of the vitamin D receptor (VDR) gene, maternal vitamin D concentration, and gestational outcomes. Methods: The cohort consisted of 270 pregnant women who received prenatal services at basic public healthcare centers in the city of Santo Antônio de Jesus, Bahia, Brazil. For statistical analysis, multiple linear regression was used. Results: A mean of 72.62 (SD = 31.51) nmol/L for 25-hydroxyvitamin D (25(OH) D) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Hence, the VDR polymorphism may be a protective or risk factor for adverse events, according to the genetic profile of the woman. 27 Our head circumference findings were similar to those of several other studies conducted in subtropical or tropical countries that demonstrated no correlation with umbilical cord blood vitamin D level. 13,[18][19][20] This study had several limitations.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, the VDR polymorphism may be a protective or risk factor for adverse events, according to the genetic profile of the woman. 27 Our head circumference findings were similar to those of several other studies conducted in subtropical or tropical countries that demonstrated no correlation with umbilical cord blood vitamin D level. 13,[18][19][20] This study had several limitations.…”
Section: Discussionsupporting
confidence: 90%
“…Vitamin D metabolism may be influenced by single nucleotide polymorphisms of VDR genes such as BsmI, FokI, TaqI, and ApaI, possibly contributing to premature birth. A Brazilian cohort study found that maternal homozygotes with the low-frequency (CD) allele of ApaI single nucleotide polymorphism may be at increased risk of preterm birth [23]. Therefore, the VDR should be considered when exploring the impact of 25(OH) D on premature delivery.…”
Section: Discussionmentioning
confidence: 99%
“…They also investigated the vitamin D levels’ association with the VDR gene’s BsmI , ApaI , and TaqI polymorphisms and their haplotypes’ distribution and their wild genotypes, and the GGT ( BAT ) haplotype correlated with lower 25(OH)D serum levels [ 92 ]. A cohort study by Pereira-Santos et al (2019) [ 93 ], with 270 pregnant women living in northeastern Brazil, evaluated the associations between VDR gene polymorphisms, maternal 25(OH)D concentration, and gestational outcomes. They found that participants with the VDR Taq I’s tt genotype had a higher 25(OH)D concentration during gestation; the children of women with the VDR Apa I SNP’s Aa genotype were born with a lower weight; women with VDR Taq I SNP’s Tt genotype decreased the risk of a shorter gestation duration; while women with VDR Apa I SNP’s aa genotype were negatively affected and had decreased gestation duration.…”
Section: Discussionmentioning
confidence: 99%